Emission scenarios of a potential shale gas industry in Germany and the United Kingdom - Lorenzo Cremonese; Lindsey B. Weger; Hugo Denier van der Gon; Marianne Pascale Bartels; Tim Butler (Elementa: Science of the Anthropocene, 2019)
The shale gas debate has taken center stage over the past decade in many European countries due to its purported climate advantages over coal and the implications for domestic energy security. Nevertheless, shale gas production generates greenhouse gas and air pollutant emissions including carbon dioxide, methane, carbon monoxide, nitrogen oxides, particulate matter and volatile organic compounds. In this study we develop three shale gas drilling projections in Germany and the United Kingdom based on estimated reservoir productivities and local capacity. For each projection, we define a set of emission scenarios in which gas losses are assigned to each stage of upstream gas production to quantify total emissions. The “realistic” (REm) and “optimistic” (OEm) scenarios investigated in this study describe, respectively, the potential emission range generated by business-as-usual activities, and the lowest emissions technically possible according to our settings. The latter scenario is based on the application of specific technologies and full compliance with a stringent  regulatory framework described herein. Based on the median drilling projection, total annual methane emissions range between 150–294 Kt in REm and 28–42 Kt in OEm, while carbon dioxide emissions span from 5.55–7.21 Mt in REm to 3.11–3.96 Mt in OEm. Taking all drilling projections into consideration, methane leakage rates in REm range between 0.45 and 1.36% in Germany, and between 0.35 and 0.71% in the United Kingdom. The leakage rates are discussed in both the European (conventional gas) and international (shale gas) contexts. Further, the emission intensity of a potential European shale gas industry is estimated and compared to national inventories. Results from our science-based prospective scenarios can facilitate an informed discussion among the public and policy makers on the climate impact of a potential shale gas development in Europe, and on the appropriate role of natural gas in the worldwide energy transition.